2020
DOI: 10.1186/s12985-020-01412-z
|View full text |Cite
|
Sign up to set email alerts
|

Favipiravir versus other antiviral or standard of care for COVID-19 treatment: a rapid systematic review and meta-analysis

Abstract: Background The COVID-19 causing coronavirus is an enveloped RNA virus that utilizes an enzyme RNA dependent RNA polymerase for its replication. Favipiravir (FVP) triphosphate, a purine nucleoside analog, inhibits that enzyme. We have conducted this systematic review and meta-analysis on efficacy and safety of the drug FVP as a treatment for COVID-19. Methods Databases like Pubmed, Pubmed Central, Scopus, Embase, Google Scholar, preprint sites, and clinicaltirals.gov were searched. The studies with the standa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 16 publications
5
66
1
3
Order By: Relevance
“…Many other drugs were repurposed like remdesivir as candidate treatment options for COVID-19. A study was done by Shrestha et al on favipiravir - another potential candidate drug that showed significant results on clinical improvement at day 14 (RR 1.41, 95% CI 1.10 to 1.80) [ 24 ]. Many other potential treatment options like corticosteroids, convalescent plasma therapy, and hydroxy-chloroquine showed mixed results in individual studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many other drugs were repurposed like remdesivir as candidate treatment options for COVID-19. A study was done by Shrestha et al on favipiravir - another potential candidate drug that showed significant results on clinical improvement at day 14 (RR 1.41, 95% CI 1.10 to 1.80) [ 24 ]. Many other potential treatment options like corticosteroids, convalescent plasma therapy, and hydroxy-chloroquine showed mixed results in individual studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the most of studies present very low-quality evidence, related to the small size of groups, the use of additional drugs, or incomplete assessment of the initial parameters of patients, the systematic review and meta-analysis carried out by Shrestha et al [ 65 ] showed a significant clinical and radiological improvement, following treatment with FVP in comparison to the standard of care, with no significant differences on viral clearance, oxygen support requirement, and side-effect profiles.…”
Section: Sars-cov-2 Infectionmentioning
confidence: 99%
“…A meta-analysis of two groups was carried out: one receiving standard care plus favipiravir and the other receiving standard care plus other regimen indicating no specific treatment benefit of favipiravir. 27 Another meta-analysis with 76 articles using remdesivir revealed that further randomized controlled trials with larger sample sizes are required to identify the best candidate components that should comprise combined treatments for COVID-19. 28 …”
Section: Discussionmentioning
confidence: 99%